2000
DOI: 10.1207/s15326942dn1801_6
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Neurobehavioral Measures of Laterality and Interhemispheric Function as Measured by Dichotic Listening

Abstract: This article presents analysis of dichotic listening performance in 57 healthy men and women aged 20 to 72 years. The data are presented as a means to cover 2 theoretical issues relevant to the biobehavioral study of laterality and interhemispheric relations. First, the sensitivity of dichotic listening performance to factors such as sex, age, and their interactions was examined. Dichotic listening asymmetry scores were found to vary as a function of sex, age, handedness, and family history of developmental la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Sex differences in dichotic listening across the life span (Cowell & Hugdahl, 2000) paralleled effects independently observed in corpus callosum anatomy (Cowell, Allen, Zalatimo, & Denenberg, 1992). Jointly, these studies (Cowell & Hugdahl, 2000;Cowell et al, 1992) suggest that as hormone levels decrease in women between the third and fifth decades of life, increases in anterior corpus callosum size may lead to less separation (i.e., greater connection) of left and right hemispheres, and, in turn, to the observed decrease in REA. In men, the anterior callosum decreased with age after the third decade of life, possibly contributing to greater separation of left and right hemispheres, and, in turn, to the increase in REA.…”
Section: Wadnerkar Whiteside Cowellmentioning
confidence: 63%
See 4 more Smart Citations
“…Sex differences in dichotic listening across the life span (Cowell & Hugdahl, 2000) paralleled effects independently observed in corpus callosum anatomy (Cowell, Allen, Zalatimo, & Denenberg, 1992). Jointly, these studies (Cowell & Hugdahl, 2000;Cowell et al, 1992) suggest that as hormone levels decrease in women between the third and fifth decades of life, increases in anterior corpus callosum size may lead to less separation (i.e., greater connection) of left and right hemispheres, and, in turn, to the observed decrease in REA. In men, the anterior callosum decreased with age after the third decade of life, possibly contributing to greater separation of left and right hemispheres, and, in turn, to the increase in REA.…”
Section: Wadnerkar Whiteside Cowellmentioning
confidence: 63%
“…Sex differences in dichotic listening, with males having a greater REA than women, have been reported in some (Cowell & Hugdahl, 2000;Weekes et al, 1995) but not all studies (Foundas et al, 2006;Hiscock et al, 1994). In the current study a significant sex difference in laterality was found only when men were compared to women at the Low-EP phase.…”
Section: Dichotic Listening and Menstrual Cycle 303mentioning
confidence: 92%
See 3 more Smart Citations